IMBALANCE OF MANAGEMENT ACCESS NATURAL RESOURCES IN AN AGRARIAN CONFLICT - Ricco Andreas (Muhammadiyah Law Review Journal, 2017)
Natural resources is one of human rights. One of the constitution basic material of 1945 is secure the human rights and the constitutional right. The constitutional right of citizens which secured within the constitution of 1945 covering various aspects such as civil , political , economic , and social. It is stated in article 33 paragraph (3)  The constitution basic of 1945.Permition access to use forest that can be used by the community is very difficult, but many mastery forest given to private sector “company”, this hamper the fell victim to sekema function transfer of forest, as investment of foresty  development. Agrarian conflict appear now, travel the distribution of land carut gods marut done by the state. In the management of access natural resources, the distribution of the state land not return lands to the community, like a spirit the constitution Number 5 years 1960, of the agrarian article 16, the state disaffirming and instead memeberikan ease to a company, on access to permit penguasan forestry resources. The conflict of forestry resource in indonesia have minimal conflict resolution, until finally it bore misery and loss of the basic rights of the community, to get a management of foresty natural resourcest, the cause of dispute on forsty sector is one of these policies governance to forest, expected as one of the conflict dispute forest in indonesia. In terms of behavior  management  by the association vie, it will produce prosperous for. It clears that why insistence on agrarian reforma not completed, Including a lack of law protection in form of the agrarian constitution renewa.